2018
DOI: 10.15446/revfacmed.v66n2.60791
|View full text |Cite
|
Sign up to set email alerts
|

Hypertriglyceridemia and adverse outcomes during pregnancy

Abstract: Introducción. Durante el embarazo, los niveles séricos de triglicéridos maternos aumentan como un mecanismo de adaptación fisiológica para suplir las necesidades del feto en desarrollo. Pese a que el incremento excesivo se ha asociado a preeclampsia, macrosomía y parto pretérmino, no se han establecido de manera contundente los niveles a partir de los cuales se deben tomar medidas en cada trimestre para prevenir complicaciones.Objetivo. Hacer una revisión sobre fisiopatología, efectos en madre e hijo, valores … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 51 publications
0
7
0
Order By: Relevance
“…Hypertriglyceridemia result in an oxidative environment leading to endothelial injury predisposing to pre-eclampsia. Furthermore, it may predispose the baby born from mother suffering from pre-eclampsia to metabolic and cardiovascular disorders in adulthood 22 . A study conducted in Egypt on cohort of n=251 pregnant women demonstrated the TG levels as predictor of pre-eclampsia between 4-12 weeks of pregnancy.…”
Section: Results Are Presented As N (%) Chi-square Test Appliedmentioning
confidence: 99%
“…Hypertriglyceridemia result in an oxidative environment leading to endothelial injury predisposing to pre-eclampsia. Furthermore, it may predispose the baby born from mother suffering from pre-eclampsia to metabolic and cardiovascular disorders in adulthood 22 . A study conducted in Egypt on cohort of n=251 pregnant women demonstrated the TG levels as predictor of pre-eclampsia between 4-12 weeks of pregnancy.…”
Section: Results Are Presented As N (%) Chi-square Test Appliedmentioning
confidence: 99%
“…Gestation is characterized by increased serum levels of total cholesterol and triglycerides pushed by estrogen, progesterone, and lactogen, which mobilize stored fat depots in late pregnancy, a pool of fatty acids for foetal growth, and placental tissue steroid synthesis. This physiologic increase in lipids performs an essential role during pregnancy; however, elevated lipids in susceptible women or familiar forms of hyperlipemia can increase maternal-foetal complications [ 41 ], and gestational hyperlipemia is associated with preeclampsia, preterm birth, and gestational diabetes, and offspring of these mothers show a propensity to enhanced fatty streak formation and an increased risk of progressive atherosclerosis [ 42 ]. It was previously demonstrated that chronically fructose-fed with diets containing high percentages of fructose develop hyperlipemia [ 43 ] and insulin resistance in pregnancy [ 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…The fetus from an AP pregnancy is exposed to the risk of threatened preterm labor, prematurity and death [7,43,44]. Regarding the follow-up of fetuses from hyperlipidemic patients, results of pathology studies performed on 6-month-old deceased fetuses of mothers with hypercholesterolemia compared to mothers with normal cholesterol levels revealed the presence of fatty streaks at aortic level [45,46].…”
Section: Fetal Implicationsmentioning
confidence: 99%